Cash for votes: Evidence from India - Anirban Mitra; Shabana Mitra; Arnab Mukherji (University of Kent, School of Economics, 2017)
This paper investigates the prevalence of vote-buying in democratic elections where stringent restrictions on corporate donations to political parties exist. We combine data from state assembly elections in India with household-level consumer expenditure surveys (conducted by NSSO) over the period 2004-11. Exploiting a difference-in-differences methodology, we estimate the effects elections have on the consumption of various household items: food, clothes, education-related, etc. Moreover, there is heterogeneity in such consumption adjustments across households. Our estimates suggest that legal sources of funds are not sufficient for generating such "spikes" in consumption and indicate the role of the hidden economy in politics.
Keywords: D12; D72; H40; 330; Political economy; election finance; black economy